2017
DOI: 10.1007/s11524-017-0185-7
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Geographic Mobility Patterns among Young Urban and Suburban Persons who Inject Drugs and their Injection Network Members

Abstract: Young people in the USA who inject drugs, particularly those at a risk of residence instability, experience the highest incidence of hepatitis C (HCV) infections. This study examined associations between geographic mobility patterns and sociodemographic, behavioral, and social network characteristics of 164 young (ages 18-30) persons who inject drugs (PWID). We identified a potential bridge sub-population who reported residence in both urban and suburban areas in the past year (crossover transients) and higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…However, relocating to neighborhoods with better social and economic conditions was associated with smaller networks of substance users and more turnover out of substance-using networks. Work in Chicago with young PWID found that crossover transience between urban and suburban places was a significant risk factor for syringe sharing and multiple sex partners, but that transience was often tied to homelessness [35,36]. Importantly, this study suggests that this movement served as a spatial bridge for HIV between higher prevalence and lower prevalence areas [35,36].…”
Section: Space Place and Networkmentioning
confidence: 70%
See 4 more Smart Citations
“…However, relocating to neighborhoods with better social and economic conditions was associated with smaller networks of substance users and more turnover out of substance-using networks. Work in Chicago with young PWID found that crossover transience between urban and suburban places was a significant risk factor for syringe sharing and multiple sex partners, but that transience was often tied to homelessness [35,36]. Importantly, this study suggests that this movement served as a spatial bridge for HIV between higher prevalence and lower prevalence areas [35,36].…”
Section: Space Place and Networkmentioning
confidence: 70%
“…New research supports the importance of network size [21], structure [22], bridging (i.e., ties connecting different groups) [23], clustering (i.e., nodes grouping together) [24], multiplexity (i.e., ties with multiple social connections, such as a sexual and drug use connection) [25][26][27], and social support and capital [28][29][30] for HIV risk behavior, transmission, viral suppression, HIV disclosure, and ART initiation. This work entails an expanded focus on populations that have historically received less attention, including research on the networks of non-injecting drug users [31,32], substance users in suburban and rural areas [22,31,[33][34][35][36], and the role of networks in newly emerging HIV outbreaks, both domestically [37][38][39] and globally [3,[40][41][42][43]. Of particular note, recent research has evolved to utilize new network concepts and to more fully account for risk environment factors that shape health.…”
Section: Overview Of Key Issues In Network Research With Substance-usmentioning
confidence: 99%
See 3 more Smart Citations